(untitled) (Conferencea, 2023)
In 2020-2023, a project dedicated to identifying diseases and pests of forest trees in the dry bottom of the Aral Sea and developing measures to combat them was implemented. As part of the project, pests and diseases that harm Haloxylon were identified and their biological properties were studied.